2012
DOI: 10.1590/s0104-77602012000300001
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfológica do fruto, semente, plântula e planta jovem e germinação de Inga ingoides (Rich) Willd

Abstract: Nesta pesquisa, objetivou-se descrever e ilustrar as características morfológicas do fruto, semente, plântula e planta jovem e germinação da espécie Inga ingoides (Rich) Willd. Utilizaram-se 100 frutos para a descrição morfológica externa, no qual observou-se: tipo, forma, comprimento, superfície, cor, deiscência, tipo de pericarpo e número de sementes por frutos. Para o estudo das características morfológicas das sementes, foram utilizadas 100 amostras, observando: forma, comprimento, superfície da testa, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(4 reference statements)
0
3
0
3
Order By: Relevance
“…For the evaluation of the young plant stage, 100 seeds were sown in a plastic tray (49 × 33 × 7 cm in length, width, and depth, respectively) drilled at the bottom, with a seeding depth of 2 cm, containing vermiculite substrate moistened at 60 % field capacity and kept in the shade for 15 d. Subsequently, the tray was placed in a greenhouse and irrigated daily for another 45 d and the evaluation of the morphological characteristics of the young plant were performed 60 d after sowing, following the methodology adapted from Braz et al (2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the evaluation of the young plant stage, 100 seeds were sown in a plastic tray (49 × 33 × 7 cm in length, width, and depth, respectively) drilled at the bottom, with a seeding depth of 2 cm, containing vermiculite substrate moistened at 60 % field capacity and kept in the shade for 15 d. Subsequently, the tray was placed in a greenhouse and irrigated daily for another 45 d and the evaluation of the morphological characteristics of the young plant were performed 60 d after sowing, following the methodology adapted from Braz et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…In the seeds of Inga ingoides (Rich.) Willd., Braz et al (2012) identified an ovate shape, ranging to oblong, some with a dark green coloration and some a lighter green, thin textured forehead, and with a smooth and shiny surface. In the study by Prado and Rodrigues (2013) of Canavalia dictyota Piper, the seeds were described as symmetrical, oblong, laterally compressed; brow glabrous, coriaceous, with a brownish-brown coloration with brown spots, opaque to slightly shiny; whereas, the seeds of Clitoria fairchildiana R.A.Howard were described as exalbuminous, orbicular, flat-convex, and brown in color (COSTA et al, 2014).…”
Section: External Morphology Of the Seedmentioning
confidence: 99%
See 1 more Smart Citation
“…O conhecimento acerca da biomorfologia da germinação, do crescimento e estabelecimento de plântulas permite uma melhor compreensão do ciclo biológico de uma dada espécie e dos processos de estabelecimento desta em seu habitat (CAMARA et al, 2008), além de auxiliar em testes de germinação em laboratório, na produção de mudas em viveiro, na dinâmica das populações e em toda área de silvicultura (BRAZ et al, 2012).…”
Section: Introductionunclassified
“…Na atualidade, em nível nacional, encontra-se alguns trabalhos científicos referentes à morfologia vegetal (LORENZI, 1992;MAIA, 2004;SOUZA & LO-RENZI, 2005;GONÇALVES & LORENZI, 2007;ARAÚJO, 2007;BRASIL, 2009;MEDEIROS, 2011;MAIA-SILVA, 2012;BRAZ et al, 2012;AGUIAR, 2013; AGUIAR, 2014; DURIGAN et al, 2018).…”
unclassified